2021
DOI: 10.1016/j.chom.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Potent SARS-CoV-2 neutralizing antibodies directed against spike N-terminal domain target a single supersite

Abstract: Highlights d Structures of seven NTD-directed neutralizing antibody complexes with spike or NTD d Structures define distinct recognition classes, one observed in multiple donors d Supersite is glycan free, electropositive, with mobile b-hairpin and flexible loops d Most potent NTD-directed neutralizing antibodies may target this supersite

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
618
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 512 publications
(645 citation statements)
references
References 94 publications
23
618
0
4
Order By: Relevance
“…Numerous neutralizing anti-RBD monoclonal antibodies (mAbs) have been characterized, the most potent of which block the RBD-ACE2 interaction (16, 17, [22][23][24][32][33][34][35][36][37]. Neutralizing against other region of the viral spike have also been identified (24,33,(38)(39)(40)(41)(42).…”
mentioning
confidence: 99%
“…Numerous neutralizing anti-RBD monoclonal antibodies (mAbs) have been characterized, the most potent of which block the RBD-ACE2 interaction (16, 17, [22][23][24][32][33][34][35][36][37]. Neutralizing against other region of the viral spike have also been identified (24,33,(38)(39)(40)(41)(42).…”
mentioning
confidence: 99%
“…To date, advanced genomic approaches have identified thousands of variants of SARS-CoV-2 with multiple RBD mutations circulating due to natural selection 16,17 . The variability of RBD epitopes is of specific concern as such mutations might reduce vaccine efficacy, increase viral transmission, or impair acquired immunity by neutralizing antibodies 10,18,19 . For the pandemic to be brought under control, herd immunity must be achieved through vaccination.…”
mentioning
confidence: 99%
“…These antibodies, identified in separate studies of infected donors from around the world ( Barnes et al., 2020 ; Hansen et al., 2020 ; Lv et al., 2020 ; Pinto et al., 2020 ) were generally chosen for study due to their neutralization potency. Overall, these studies identified antibodies mainly targeting RBD ( Brouwer et al., 2020 ; Shi et al., 2020 ; Tortorici et al., 2020 ; Wu et al., 2020 ), with some NTD-directed neutralizers ( Cerutti et al., 2021 ; Chi et al., 2020 ), with antibodies of the same class often identified in multiple studies. The residue-level antibody-interaction frequencies we present for RBD are likely to represent a reasonable estimate of relative frequencies, but only for the most potent and most frequent classes.…”
Section: Discussionmentioning
confidence: 99%
“…SARS CoV-2 S2P spike density was modeled using PDB entry 7L2E ( Cerutti et al., 2021 ), as initial template. The initial model for 1-57 Fab variable region was obtained using the SAbPred server ( Dunbar et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%